EU Smart Cities: Towards a New Framework of Urban Digital Transformation (Informatica, 2023)
The URBANITE H2020 project aims to address urban mobility challenges caused by growth and new transportation methods. It develops a decision support system for policymakers, incorporating simulation, evaluation of key performance indicators (KPIs), a recommendation/decision support system (DSS), and machine learning (ML) capabilities. The system helps identify and improve KPIs, proposes effective policies, and enhances urban digital transformation for sustainable and efficient mobility